Biodiversity of Insect Larvae in Streams at Jobolarangan Forest - EDWI MAHAJOENO; MANAN EFENDI; ARDIANSYAH ARDIANSYAH (Biodiversitas Journal of Biological Diversity, 2001)
Insect larvae are macro-invertebrate that becomes the most perfect indicator of aquatic-environmental health. Natural streams usually determined by its insect-larvae community in a good condition, in which their taxonomic diversity and richness are high. The objective of the research was to know the taxonomic diversity and richness of insect-larvae family in streams at Jobolarangan forest. The larvae were sampled using net-surber (dip-net) in three location of streams, i.e.: Parkiran (1773 m asl.), Mrutu (1875 m asl.), and Air Terjun (1600 m asl.). The screened insect-larvae were grouped its family and counted their individual number. The diversity was counted using Shanon-Weiner diversity indices. In this research was found 12 families of insect-larvae consisted of two families of Odonata order, 3 families of Coleopteran order, and a family of Lepidoptera. Nine families identified, while the three insect-larvae i.e. 2 of Coleoptera and 1 of Lepidoptera were not identified yet. The Parkiran station indicated the highest diversity index of 0.1436.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: insect-larvae, diversity, streams, Jobolarangan